2009
DOI: 10.1007/s12594-009-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical assessment of groundwater around Macherla-Karempudi area, Guntur district, Andhra Pradesh

Abstract: Groundwater in Palnad sub-basin is alkaline in nature and Na + -Cl --HCO 3 type around Macherla-Karempudi area in Guntur district, Andhra Pradesh. Total dissolved solids (TDS) show strong positive correlation with Cl -, Na + , Ca 2+ and Mg 2+ , and positive correlation with SO 4 2-, K + and HCO 3 -. Calcareous Narji Formation is the dominant aquifer lithology, and water-rock interaction controls the groundwater chemistry of the area. Chloro-alkaline indices (CAI) are positive at Miriyala, Adigopula, Mutukuru, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Geochemical processes, occurring within the groundwater and their reactions with the aquifer materials, are responsible for changes in groundwater chemistry (Drever 1988;Hem 1991;Wen et al 2008;Subba Rao and Surya Rao 2009). Geochemical studies of groundwater provide a better understanding of possible changes in quality as development progress (Sreedevi 2004;Jalali 2006;Nagaraju et al 2006;Subba Rao 2006;Gupta et al 2008Gupta et al , 2009Bhardwaj et al 2010). Urbanization and related anthropogenic activities also affect the groundwater quality (Whittemore et al 1989;Mondal et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geochemical processes, occurring within the groundwater and their reactions with the aquifer materials, are responsible for changes in groundwater chemistry (Drever 1988;Hem 1991;Wen et al 2008;Subba Rao and Surya Rao 2009). Geochemical studies of groundwater provide a better understanding of possible changes in quality as development progress (Sreedevi 2004;Jalali 2006;Nagaraju et al 2006;Subba Rao 2006;Gupta et al 2008Gupta et al , 2009Bhardwaj et al 2010). Urbanization and related anthropogenic activities also affect the groundwater quality (Whittemore et al 1989;Mondal et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Subbarao et al (1996) used factor analysis to characterize the groundwater contamination by industrial effluents in a single hydrogeological unit. Gupta et al (2009) carried out geochemical assessment of groundwater with reference to water-rock interaction and suitability of groundwater quality in respect of drinking and irrigation purposes around Macherla-Karempudi area of south India. Hydrochemical studies conducted on groundwater quality of Solapur city revealed that dug wells are more polluted than bore wells and the groundwater contamination is mainly due to anthropogenic activities (Naik et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2) and Table 2 show that although in the majority of river water samples Ca 2+ + Mg 2+ exceed Na + + K + , in most of the groundwater samples, the contribution of alkalis (Na + + K + ) exceeds alkaline earths (Ca 2+ + Mg 2+ ). In these samples, sodium drives from natural ion exchange where Na-montmorilonite clay reacts with calcium and magnesium and releases sodium into the water (Gupta et al 2009). …”
Section: Piper Diagrammentioning
confidence: 99%
“…Criteria like magnesium ratio, Gibbs' ratio, Piper diagram, and US Salinity Laboratory diagrams are used to assess the nature of water and its suitability for irrigation (Rao 2006;Singh et al 2008;Gupta et al 2008Gupta et al , 2009Giridharan et al 2009;). …”
Section: Introductionmentioning
confidence: 99%
“…Hydrogeochemical investigations are conducted to identify groundwater evolution, recharge and extent of pollution in Friuli Venezia Giulia Plain Aquifers (Italy; Cucchi et al 2008). Geochemical assessment of groundwater with reference to water-rock interaction and suitability of groundwater quality in respect of drinking and irrigation purposes are studied around Macherla-Karempudi area, Guntur District, Andhra Pradesh (India) by Gupta et al (2009).…”
Section: Introductionmentioning
confidence: 99%